Competences Helping to Increase Students’ Prophylaxis Competence in Medical Education and their Characteristics - Mirovich, Turdiyev Shavkat Ma (Journal of Innovation in Education and Social Research, 2025)
This article explores the core competencies that contribute to the development of students' prophylactic competence in medical education. It highlights how these competencies - such as critical thinking, communication, health promotion, and ethical responsibility - play a vital role in preparing future healthcare professionals for effective disease prevention and health education.